21st Century Outbreaks (Turkey Health Literacy Journal, 2021)
An epidemic is defined as the occurrence of a disease in a certain region, in a certain time interval, more than expected or aggregation due to certain common characteristics. 21st century epidemic diseases were examined as new and redefined infectious diseases, noncommunicable chronic degenerative diseases and mental health diseases. In the subtitles of these diseases; diabetes, heart diseases, cancers, chronic respiratory diseases, Alzheimer’s, depression, anxiety, internet and game addiction, eating disorders, child abuse, substance addiction, AIDS, Yellow Fever, Typhoid, Shigella, Meningococcus, COVID-19 virus, zoonotic influenza viruses are considered and described as Chikungunya virus, Crimean Congo Hemorrhagic Fever virus, Zika virus and MERS viruses are thought and explained. Dietary and lifestyle changes that occur with the changes of today’s living conditions, increasing transportation and communication around the world, social determinants of health and inadequate health literacy are discussed as the main reasons for the increase of communicable and non-communicable diseases. In this review, it is aimed to present an up-to-date approach by mirroring the COVID-19 virus pandemic and other epidemics in the 21st century.